Induction of the cell survival kinase Sgk1: A possible novel mechanism for α-phenyl-N-tert-butyl nitrone in experimental stroke. Issue 6 (June 2019) - McCaig, Catherine; Ataliotis, Paris; Shtaya, Anan; Omar, Ayan S; Green, A Richard; Kind, Clive N; Pereira, Anthony C; Naray-Fejes-Toth, Aniko; Fejes-Toth, Geza; Yáñez-Muñoz, Rafael J; Murray, James T; Hainsworth, Atticus H
Nitrones (e.g. α-phenyl-N-tert-butyl nitrone; PBN) are cerebroprotective in experimental stroke. Free radical trapping is their proposed mechanism. As PBN has low radical trapping potency, we tested Sgk1 induction as another possible mechanism. PBN was injected (100 mg/kg, i.p.) into adult male rats and mice. Sgk1 was quantified in cerebral tissue by microarray, quantitative RT-PCR and western analyses. Sgk1 +/+ and Sgk1 −/− mice were randomized to receive PBN or saline immediately following transient (60 min) occlusion of the middle cerebral artery. Neurological deficit was measured at 24 h and 48 h and infarct volume at 48 h post-occlusion. Following systemic PBN administration, rapid induction of Sgk1 was detected by microarray (at 4 h) and confirmed by RT-PCR and phosphorylation of the Sgk1-specific substrate NDRG1 (at 6 h). PBN-treated Sgk1 +/+ mice had lower neurological deficit ( p < 0.01) and infarct volume ( p < 0.01) than saline-treated Sgk1 +/+ mice. PBN-treated Sgk1 −/− mice did not differ from saline-treated Sgk1 −/− mice. Saline-treated Sgk1 −/− and Sgk1 +/+ mice did not differ. Brain Sgk3:Sgk1 mRNA ratio was 1.0:10.6 in Sgk1 +/+ mice. Sgk3 was not augmented in Sgk1 −/− mice. We conclude that acute systemic treatment with PBN induces Sgk1 in brain tissue. Sgk1 may play a part in PBN-dependent actions in acute brain ischemia.